NURSING CARE IN THE IMMEDIATE POSTOPERATIVE PERIOD OF CARDIAC SURGERY (Fiep Bulletin - online, 2013)
Nursing assistance in the immediate postoperative period of cardiac surgery is destined to interventions designated to prevent or treat complications, promoting a fast recovery and reducing costs, preoccupations, pain and increasing patient survival. Objective: to know the nursing assistance provided in the immediate postoperative period of cardiac surgery. Methods: it is an exploratory-descriptive and field study, with quantitative approach. It was developed in the Cardiologic Unit of a private hospital in João Pessoa-PB. The population was constituted by all inpatients in this service, composing a sample of 9 inpatients in the period between October and November 2011. The data were collected from medical records, using a structured questionnaire with objective and subjective questions. After, they were analyzed using SPSS software, version 19.0. The description was presented by means of absolute and percentage frequency. The research was approved by the Ethics Research Committee of the Institute of Higher Education of Paraíba (IESP), under number 011/2011. Results: the feminine sex prevailed with 55.5%. In relation to age group, 88.8% of patients were over 60 years and only 11.2% were between 41 to 50 years. Considering ethnicity, white people prevailed with 66.7% of cases. The most predominant risk factors was family history, with 66.7% of cases, followed by sedentariness and tobaccoism with 55.5% each. Coronary insufficiency was the most present (44.4%), followed by diabetes mellitus (22.2%) and hypertension (22.2%). Among the studied patients, coronary artery bypass grafting (CABG) was the most incident procedure (77.7%). The nursing staff was involved in all the procedures done in the immediate postoperative period. Conclusion: nursing assistance contemplates the realization of many procedures that require knowledge, technical skill, dexterity and demand much time of the staff. However, some of these procedures are underreported.
Keywords: Nursing assistance; Cardiac surgery; Surgical nursing.